EU cooperation with non-member neighboring countries: The principle of variable geometry - Marek Dabrowski (Center for Social and Economic Research (CASE), 2014)
The European Union (EU) represents a large and highly integrated bloc which contributed 19.4% of global GDP and over 30% of global exports in 2012. As of July 1, 2013 it consists of 28 member states. All of them belong to the customs union and the Single European Market (SEM) in which most formal and informal barriers to the free movement of goods, services, people and capital have been removed. In addition, most members share a common currency (Euro) and form a free-travel Schengen zone. The important policy areas such as external trade, customs, competition, other regulations related to SEM, monetary policy (in the case of the Eurozone), certain iscal and other macroeconomic policies, part of indirect taxation, research, energy policy, etc. have been transferred to the competence of supranational EU bodies. Several other questions such as immigration and asylum, visas, common border management, justice and home affairs, and foreign and security policy remain subject to coordination and common decisions. [...]
Keywords: F13; F15; F55; N74; 330; integration; European Union; association agreement; free trade agreement; EU enlargement; European Neighborhood Policy